Correlation of Serum and Gingival Crevicular Fluid Levels of Caspase-3 and Milk Fat Globule-Epidermal Growth Factor 8 on Gingival Health - Manonmani Pavithra Ravindran; A Geetha; Sathish Rajendran; Jaideep Mahendra; M Jyothi; Ambalavanan Namasivayam (Wolters Kluwer Medknow Publications, 2024)
Aim: This study aimed to estimate and correlate the serum and gingival crevicular fluid (GCF) levels of caspase-3 and milk fat globule-epidermal growth factor 8 (MFG-E8) in healthy, gingivitis and generalised chronic periodontitis subjects. Materials and Methods: A total of 24 subjects were selected and divided into three groups. After recording the periodontal parameters (plaque index (PI), modified gingival index (MGI), probing depth (PD) and clinical attachment level (CAL)), the serum and GCF samples were collected and the levels of caspase-3 and MFG-E8 were estimated using enzyme-linked immunoassay (ELISA). Results: The mean values of PI, MGI, PD and CALs were significantly higher in group III when compared to group II and group I. The mean value of serum and GCF caspase-3 increased with increasing disease severity, whereas the mean serum and GCF values of MFG-E8 decreased with increasing severity of disease. Spearman's correlation showed a strong positive correlation between the serum and GCF levels of caspase-3 and periodontal parameters, whereas serum and GCF levels of MFG-E8 showed a strong negative correlation with the periodontal parameters. Conclusion: The findings of this study are suggestive that the serum and GCF levels of caspase-3 and MFG-E8 could serve as a potential biomarker for the role of apoptosis in periodontal disease. However, further studies are required to explore the mechanism and understand the relationship between these apoptotic markers and periodontitis.